Pengaruh Berbagai Media Tanam terhadap Pertumbuhan dan Hasil Jamur Tiram (Pleurotus Ostreatus) - Nur Hafizah; Aspiani Aspiani (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2016)
Oyster mushrooms cultivation requires media to resemble the natural habitat of the fungus. Media in Indonesia are usually called by baglog. This study aims to (i) the effect of a variety of growing media on growth and yield of oyster mushroom, and (ii) obtain the best growing media in the growth and yield of oyster mushroom. This research was conducted in Kias Village of Batang Alai District of South Hulu Sungai Tengah South Kalimantan Province, in May until August 2013, using a completely randomized design (CRD), with three treatments and six replications. Each quiz consists of 3 samples. Factors to be examined is the composition of reeds s1 = 80%: 18% bran: 1%, lime: 1% gypsum. s2 = 80% of rice straw: 18% bran: 1%, lime: 1% gypsum. s3 = 80% sawdust: 18% bran: 1%, lime: 1% gypsum. The results showed that the composition of the media influence on a growing number of fruit bodies, wet weight and no effect on the maximum diameter hood fruit treated with the best composition obtained on the composition s3 = 80% sawdust: 18% bran: 1%, lime: 1% casts.